The relationship between sarcopenia and central hemodynamics in older adults with falls: a cross-sectional study. Issue 2 (26th October 2021) - Öztorun, Hande Selvi; Bahsi, Remzi; Turgut, Tugba; Surmeli, Deniz Mut; Cosarderelioğlu, Caglar; Atmis, Volkan; Yalcin, Ahmet; Aras, Sevgi; Varli, Murat
Abstract : Supplemental Digital Content is available in the text. Abstract : Purpose: Falls are an important cause of morbidity and mortality in geriatric patients. Sarcopenia and central blood pressure may be associated with falls. This study aimed to investigate the association between sarcopenia and blood pressure parameters in older patients with falls. Methods: A comprehensive geriatric evaluation of 72 elderly patients was performed using established assessment tests. Peripheral and central hemodynamic measurements, including office DBP and SBP, daytime-night peripheral and central DBP and SBP, cardiac output, augmentation index, pulse wave velocity (PWV), pulse rate, and peripheral resistance and reflection, were measured with a 24-hour ambulatory blood pressure measuring device. Results: Of 72 patients with a mean age of 77.51 ± 6.5 years, 12 (16.7%) were non-sarcopenic, 32 (44.4%) were probable, nine (12.5%) were confirmed, and 19 (26.4%) were severe sarcopenic. PWV, which is an indicator of arterial stiffness, was found to be significantly higher in the sarcopenic group. The other cardiac risk markers [daytime peripheral SBP, mean arterial pressure (night), pulse pressure (daytime), and peripheral resistance (daytime and night)] were significantly lower in the sarcopenic patients. PWV correlated with gait speed, Katz score, and hand grip strength (Spearman's rho: −0.337, −0.310, and −0.334; P < 0.001, 0.008, and 0.001, respectively). Age and hypertension were the most important factors increasing the risk of falls. Conclusion: Sarcopenia is associated with central and peripheral blood pressure changes in patients with falls. When sarcopenia is diagnosed in older people with falls, 24-hour ambulatory peripheral and central pressures should be evaluated for cardiac risk screening.